Enhancing Students’ Health Literacy Through PBL-CMM: An Innovative Approach in High School Biology Education - Salim, Fitrah Amalia; Mahanal, Susriyati; Susanto, Hendra; Hardianto, Hardianto; Kusmahardhika, Noviansyah (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2025)
The enhancement of students’ health literacy represents a pivotal element in preparing them to confront contemporary health challenges. Accordingly, this study evaluates the impact of a combined problem-based learning and collaborative mind mapping (pbl-cmm) framework on improving students’ capacities for health literacy. Conducted with 110 senior high school students in Parepare, Indonesia, this quasi-experimental study employed a pretest–posttest non-equivalent control group design focused on the excretory and reproductive system topics in biology. Three groups were compared: PBL-CMM, PBL only, and conventional learning. Health literacy was measured through the Biology-Related Health Test (BRHT) and the Health Literacy Questionnaire (HLQ), which were developed based on four literacy dimensions: access, understand, appraise, and apply. The ANCOVA results revealed that students in the PBL-CMM group achieved significantly higher health literacy scores (corrected mean = 77.70) than those in the PBL (65.09) and conventional groups (56.20), p < .05. Similarly, the BRHT scores showed consistent patterns (PBL-CMM = 78.17; PBL = 70.26; Conventional = 65.95). The findings suggest that the PBL-CMM model is effective in fostering comprehensive health literacy through collaborative, problem-centered learning strategies. Future research is recommended to apply this model across diverse educational contexts, larger student populations, and different subject areas to examine its broader applicability and long-term impact on students’ critical thinking and decision-making in health-related issues